Wolność myśli, sumienia i wyznania w prawie polskim. Próba analizy pojęć – określenia zakresu - Sobczak, Witold (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2012)
The issue of religious schools being financed from public resources in Poland needs to be approached primarily from the point of view of the constitutional guaranties of the freedom of conscience and religion. To this end the regulations of the Law of May 17, 1989 on the guarantees of the freedom of conscience and religion need to be analyzed together with the Law on the relations between the Republic of Poland and the Roman Catholic Church that was passed on the same day. It is only then that the following regulations should be considered: the concordat between the Holy See and the Republic of Poland signed in Warsaw on July 28, 1993, the Law of June 14, 1991 on financing the Catholic University in Lublin from the state budget, and the Law of June 26, 1997 on financing the Papal Theological Academy in Krakow from the state budget. The latter institution presently operates under the name of the Pontifical University of John Paul II. Finally, an analysis is required of a group of three laws of April 5, 2006 on financing the Papal Theological Faculty in Warsaw, Papal Theological Faculty in Wrocław and Jesuit University of Philosophy and Education “Ignatianum” in Cracow respectively.
The problems related to religious schools being financed from public resources as opposed to the freedom of conscience and religion in the political system of Poland